Do accident and emergency patients collect their prescribed medication?. Issue 1 (March 1985) - Freeman, C P; Guly, H R
Abstract : One month's prescriptions from an accident and emergency department were examined. Of these 16% were found not to have been dispensed by the chemist. The commonest drugs prescribed were antibiotics (60%) and analgesics (22%). Most age groups were guilty of failing to collect drugs--primary non-compliance.